2021
DOI: 10.34172/jlms.2021.47
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Effects of Antimicrobial Photodynamic Therapy With an LED and a Laser on the Proliferation of Human Gingival Fibroblasts on the Root Surface: An In Vitro Study

Abstract: Introduction: This study aimed to compare the effects of root biomodification by citric acid and antimicrobial photodynamic therapy (aPDT) with LED and laser on the proliferation of human gingival fibroblasts (HGFs). Methods: This in vitro experimental study evaluated 60 single-rooted teeth extracted due to periodontal disease. The teeth underwent scaling and root planing (SRP), and then 5 × 5 mm blocks were prepared from the cervical area of the teeth 1 mm apical to the cementoenamel junction. The blocks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The optimum pain perception of patients could be attained after active periodontal treatment. Additionally, other therapies such as ozone [ 35 ], laser photodynamic therapy [ 36 ], and regenerative materials [ 37 ] could have a significant influence on the oral environment. These therapies could modify clinical and microbiological parameters in periodontal patients and could have an effect on pain assessment in combination with SRP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The optimum pain perception of patients could be attained after active periodontal treatment. Additionally, other therapies such as ozone [ 35 ], laser photodynamic therapy [ 36 ], and regenerative materials [ 37 ] could have a significant influence on the oral environment. These therapies could modify clinical and microbiological parameters in periodontal patients and could have an effect on pain assessment in combination with SRP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other therapies can have a significant influence on the oral environment. The use of ozone and laser photodynamic therapies can modify clinical and microbiological parameters in periodontal patients, and they could also have an effect in the response to the technique described in the present report [ 36 , 37 ]. As in our study, it was found that a mixture of black seeds oil and powder can be effectively used as an alternative to Alvogyl in patients suffering from dry socket.…”
Section: Discussionmentioning
confidence: 99%
“…aPDT involves photoexcitation, which occurs when a photosensitiser (PS) dye is illuminated by a light of a matched wavelength, resulting in its activation and stimulation of a phototoxic response in the presence of ambient oxygen 4. The main advantages of aPDT over the conventional antimicrobial therapies include the immediate onset of action, elimination of resistant microorganisms, local delivery of the PS and double selectivity (deleterious effect only on sites where both PS and light are delivered concomitantly) 5. The use of aPDT for the decontamination of dental biofilm and periodontal pockets has been assessed in vitro,2 in systematic reviews1 4 and in randomised clinical trials 3 6.…”
Section: Introductionmentioning
confidence: 99%
“… 4 The main advantages of aPDT over the conventional antimicrobial therapies include the immediate onset of action, elimination of resistant microorganisms, local delivery of the PS and double selectivity (deleterious effect only on sites where both PS and light are delivered concomitantly). 5 The use of aPDT for the decontamination of dental biofilm and periodontal pockets has been assessed in vitro, 2 in systematic reviews 1 4 and in randomised clinical trials. 3 6 Some studies have even addressed the issue of COVID-19 and how aPDT could aid in oral decontamination, including prior to dental procedure, diminishing the risks of cross-infection.…”
Section: Introductionmentioning
confidence: 99%